A retrospective analysis with quality of life assessment of nasal surgery for nasal obstruction - Karakus, Mehmet Fatih; Karakurt, Suleyman Emre; Colak, Mustafa (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Nasal obstruction is a common health problem that disrupts a person’s quality of life (QoL). The Nasal Obstruction Symptom Evaluation scale (NOSE) is a QoL scale with questions specific to nasal obstruction symptoms. This study aimed to evaluate surgical success in patients who underwent nasal septal deviation surgery by using a NOSE assessment, thus determining the importance and efficacy of surgery in this group of patients. Methods: This study was conducted in between January 2016 and June 2017, including a total of 60 patients. The age range of the patients was 18–57 (mean, 34.4±9.9 years). The preoperative and postoperative scoring and surgeries were performed by the same investigator. The surgeries were septoplasty and radiofrequency applied to the inferior concha to overcome conchal hypertrophy. Preoperative mean scores were compared with postoperative second-month values. The importance of difference was evaluated with the Wilcoxon signed-rank test. Results: Preoperative minimum, maximum and mean scores were 65.0, 100.0 and 83.4 (83.41±8.15), respectively. Postoperative minimum, maximum and mean scores were 10.0, 35.0 and 21.6 (21.66±8.06), respectively. The difference in mean scores was significant (Z=−6.778; p<0.001). Conclusions: The difficulty in evaluating patient satisfaction and postoperative success stems from differences in each surgeon’s approach and the comparison of preoperative and postoperative findings. This study, which was carried out by the same researcher for all steps, differs it from similar studies.